2003
DOI: 10.1053/rmed.2003.1438
|View full text |Cite
|
Sign up to set email alerts
|

Impact of comorbidities on the duration of COPD patients' hospital episodes

Abstract: The duration of inpatient episodes due to COPD and the factors that affect it have recently been an object of increasing attention, as the aim has been to shorten inpatient periods and thereby to cut health-care costs. All hospital episodes of patients aged over 45 for a primary diagnosis of COPD equal or less than 150 days in duration were drawn from the treatment register maintained by the National Research and Development Centre for Welfare and Health. The lengths of these 152569 inpatient periods were anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
1
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 9 publications
2
19
1
1
Order By: Relevance
“…Surprisingly and contrary to some previous studies [4,5,6,7,8,9,17,18], age and comorbidities did not affect outcome, nor even did cardiovascular diseases, which were highly prevalent in our cohort. This is consistent with Anzueto [36] reporting that cardiac comorbidity is a risk factor for poor outcome in moderate COPD patients, but impairment of respiratory function prevails over cardiac disease in more severe COPD (our patients were hospitalised for an exacerbation and 76% were in GOLD stage III or IV).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Surprisingly and contrary to some previous studies [4,5,6,7,8,9,17,18], age and comorbidities did not affect outcome, nor even did cardiovascular diseases, which were highly prevalent in our cohort. This is consistent with Anzueto [36] reporting that cardiac comorbidity is a risk factor for poor outcome in moderate COPD patients, but impairment of respiratory function prevails over cardiac disease in more severe COPD (our patients were hospitalised for an exacerbation and 76% were in GOLD stage III or IV).…”
Section: Discussioncontrasting
confidence: 99%
“…Some of the most frequently recognised predictors of mortality are higher age, lower BMI, lower FEV 1 , hypercapnia, hypoxaemia, hypoalbuminaemia, comorbidity, cor pulmonale, previous exacerbations or admissions, LTOT and severity of dyspnoea [4,5,6,7,8,9,10,11,12,13]. Furthermore, factors associated with prolonged hospitalisations include higher respiratory rate, dyspnoea, comorbidity, cor pulmonale and weekend admission [12,16,17]. Readmissions after hospitalisation for an exacerbation are frequent events, ranging from 14 to 16% in the first month after discharge and 25–58% in the first year [5,19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8,9,20,28,29 It is reasonable to expect stay to be longer in subjects with multiple underlying health conditions. A Charlson comorbidity index score Ն 3 in our study identified subjects with prolonged stay.…”
Section: Discussionmentioning
confidence: 99%
“…Co-morbid conditions, such as cardiovascular disease often coexist with COPD, leading to worse outcomes 2 . Both co-morbidity and increasing age are associated with less effective COPD self-management 3 , more frequent hospitalisation 4 and higher mortality [5][6][7] .…”
Section: Introductionmentioning
confidence: 99%